Preoperative Changes in Hematological Markers and Predictors of Glioma Grade and Survival - Wang, Peng-Fei; Meng, Zhe; Song, Hong-Wang; Yao, Kun; Duan, Ze-Jun; Yu, Chun-Jiang; Li, Shou-Wei; Yan, Chang-Xiang (Frontiers in Pharmacology, 2018)
Background: Preoperative hematological markers that indicate nutritional, coagulation, and inflammation statuses have prognostic value for gliomas. This study aimed to investigate hematological markers with regards to tumor grades, isocitrate dehydrogenase mutations (IDH), age, and sex in patients with gliomas. Methods: From 2008 to 2017, patients with a pathological diagnosis of glioma who underwent surgery were retrospectively enrolled in this study. Information from clinical records, including age, sex, preoperative experiment tests (routine blood tests, biochemistry, and coagulation examinations), pathological results, and IDH status, was collected. A univariable survival analysis was performed. Hematological factors such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte-ratio (PLR), and albumin-to-globulin (AGR) were calculated. The prognostic nutrition index (PNI) was calculated as 10 × serum albumin value (g/dl) + 0.005 × peripheral lymphocyte count (per mm3). Results: Our study included 706 patients. The univariate analysis showed that age, IDH-1, and hematological factors were all significantly associated with overall survival (OS) in patients with gliomas. Our results showed that inflammation markers (NLR, PLR, and fibrinogen) were positively associated with age, while AGR was negatively associated with age. The PLR was significantly increased, while the AGR and PNI were decreased in females with gliomas, as compared with males. We found that inflammation markers increased and nutrition markers decreased with gliomas grade. However, these hematological markers did not significantly differ with IDH status. NLR was the best single hematological marker for distinguishing glioblastoma (GBM) [0.684 (0.645-0.723)], IDH-wt GBM [0.672 (0.631-0.71)]. Combinations of age with PNI and age with AGR were the best predictors of GBM [0.712 (0.672-0.751)] and IDH-wt GBM [0.711 (0.669-0.753)], respectively. Conclusion: Preoperative hematological marker levels vary among glioma grades and have high predictive values for GBM.